Phytochemical properties and antibacterial activity of green tea leaf extract from gunung gambir jember against Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans: an experimental study - Meilawaty, Zahara; Ermawati, Tantin; Sari, Desi Sandra; Ningsih, Indah Yulia; Rachmawati, Dessy; Nulend, Jenneke Klein (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Green tea leaves are abundant in bioactive components, including catechins, flavonoids, and polyphenols. These compounds are known for their antibacterial, anti-inflammatory, and antioxidant properties. In addition, green tea also contains minerals, such as Calcium, Phosphor, Potassium, Magnesium, and Sulphur. However, the precise mineral content and anti-bacterial properties of green tea against Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans from Gunung (Mount) Gambir in Jember Regency are currently unknown. This study aimed to analyze the phytochemical composition and antibacterial activity of green tea leaf extract from Gunung Gambir, Jember against Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans. Methods: The bioactive constituents of green tea leaf extract were identified using a UV-Vis spectrophotometer to measure its total flavonoid content (TFC) and total phenolic compounds (TPC). Mineral identification was performed using flame atomic absorption spectrometry. The disc diffusion method was used to assess antibacterial activity by quantifying the diameter of the inhibition zone in cultures of Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans treated with green tea leaf extract at concentrations of 3.125%, 6.25%, 12.5%, 25%, 50%, and 100%. Anaerobic conditions were created by incubating the Petri dishes in a desiccator for 24 hours at 37°C. One-Way Anova test was used to analyze the data, and differences were considered statistically significant at p<0.05. Subsequently, a LSD test was carried out (p<0,05). Results: The TPC value was 1.607±0.742 mg GAE/g, while the TFC value was 99.146 ± 0.307 mg GAE/g. Calcium appeared to be the most abundant mineral in the tea extract, measured at 31.65 ppm. The inhibitory power of green tea leaves extract against both bacteria was not significantly different (p>0.05). Conclusion: Green tea leaves extract from Gunung Gambir Jember Regency in Indonesia is rich in phenolic compounds, flavonoids, and certain minerals, such us Phosphor, Calium, Magnesium, Sulphur and Calcium. These constituents are known to possess biological and antibacterial activity against Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans.KEYWORDS Antibacterial, flavonoid, green tea extract, minerals, phenol, Jember